Class III Malocclusion Camouflage Treatment Using a Conventional Orthodontic Appliance in a Non-Growing Patient - Monika, Fransiska; Widayati, Retno (Journal of Dentistry Indonesia, 2023)
The treatment of skeletal and dental Class III malocclusions is a challenge for orthodontists, and one of the treatment alternatives for a non-growing patient is orthodontic camouflage treatment. Different approaches may result in different outcomes; therefore, a proper diagnosis and treatment plan are needed to avoid undesirable effects. In this case, a 21-year-old female patient presented with a skeletal Class III malocclusion, with a normal maxilla, prognathic mandible, moderate crowding, and an acceptable facial profile. The treatment modality for orthodontic camouflage treatment was a conventional orthodontic appliance with the extraction of mandibular first premolars to resolve crowding. At the end of the treatment, a Class I canine and incisor relationship was achieved while maintaining a Class III molar relationship. After 25 months of treatment, the patient had a more pleasant smile with improved functional occlusion.